OPTIMALISASI MODEL PAKEM UNTUK PENINGKATAN KEMAMPUAN ILMU PENGETAHUAN SOSIAL SISWA KELAS VI SD - Dwi Istati Rahayu (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2013)
Abstract: Optimalization of Pakem Model to Improve Sixth Grade Students’ Social Studies Learning Competencies. The purposes of this research were (1) to improve sixth grade students’ social studies learning competencies through application pakem model, and (2) to improve optimalisation activeness, creativity, effectiveness, and enjoyment teaching model. Research method used was descriptive, classroom action model, with two cycles. Research subjects were sixth grade of 18 state elementary schools Mataram. Result showed that the application of pakem model optimalized improvement sixth grade students’ social studies learning competencies activeness, creativity, effectiveness, and enjoyment in teaching. The application of pakem model improved teachers motivation and competencies in implementing teaching, and it also improved students’ cognitive, affective, and psycho-motor competency. Abstrak: Optimalisasi model pakem untuk peningkatan kemampuan ilmu pengetahuan sosial siswa kelas VI SD. penelitian ini bertujuan untuk (1) meningkatkan kemampuan belajar Ilmu Pengetahuan Sosial siswa kelas VI dengan diterapkannya Model Pakem, (2) meningkatkan optimalisasi keaktifan, kreativitas, keefektifan, dan kenyamanan model pembelajaran. Penelitian model tindakan kelas ini dilakukan dua siklus. Subyek penelitian siswa kelas VI SDN 18 Mataram. Hasil penelitian menunjukkan bahwa penerapan model Pakem dalam pelajaran IPS di kelas VI dapat mengoptimalkan peningkatan kemampuan keaktifan, kreatifitas, keefektifan dan juga kenyamanan dalam pembelajaran. Penerapan model Pakem dapat meningkatkan antusias dan kemampuan guru dalam pelaksanaan pembelajaran, serta mampu meningkatkan kemampuan kognitif, afektif dan psikomotorik siswa. Kata Kunci: model pakem, kemampuan IPS, Siswa SD